The Effect of Word of Mouth, Advertising Using Selebgram, and Paid Promote on Purchase Decisions at Ayam Geprek Mang Soetta Gresik - Dhiemas Arya Putra; Sukaris Sukaris (Universitas Muhammadiyah Gresik, 2022)
This study aims to determine the effect of Word of Mouth (WOM), advertising using Selebgram, dan Paid Promote to purchasing decision at Ayam Geprek Mang Soetta Gresik. Effective marketing is one of the keys to the success of a business. For this reason, this study was conducted to determine several variables related to marketing and purchasing decisions. This type of research is quantitative research. Using a questionnaire method with incidental sampling techniques and with a sample of 100 consumers of AGMS Gresik. Testing using the SPSS method. The results show that word of mouth (WOM), advertising using Selebgram, and paid promotion have a positive influence on purchasing decisions at Ayam Geprek Mang Soetta Gresik.